Regularity results for Kolmogorov equations in $L^2 (H, μ)$ spaces and applications - Da, Prato G.; Да, Прато Г. (Institute of Mathematics, NAS of Ukraine, 1997)
We consider the transition semigroup $R_t =e^{tsA}$ associated to an Ornstein—Uhlenbeck process in a Hilbert space $H$. We characterize, under suitable assumptions, the domain of $A$ as a subspace $W^{2,2} (H, μ)$, where $μ$ is the invariant measure associated to $R_t$. This characterization is then used to treat some Kolmogorov equations with variable coefficients.